The long shore archaeologies and social histories of Californias maritime cultural landscapes - Meniketti, Marco G. 1954- (Berghahn, 2023)
The archaeology of maritime cultural landscapes offers insights into cultural traditions, social transitions, and cultural relationships that reach beyond the narrow confines of waterfronts and beach strands and helps construct meaningful social histories. The long shore of California is not limited to the land that borders the Pacific Ocean, but includes the navigable waters that reach inland, the off-shore islands, and the riverways flow to the sea. Authors investigate the multifaceted character of maritime landscapes and maritime oriented communities in California's equally diverse cultural landscape; viewed through an archaeological lens, and emphasizing social behavior and community as material culture in order to reveal intersections and commonalities